Cathepsin K null mice show reduced adiposity during the rapid accumulation of fat stores. - Marcella Funicello; Michela Novelli; Maurizio Ragni; Teresa Vottari; Cesare Cocuzza; Joaquin Soriano-Lopez; Chiara Chiellini; Federico Boschi; Pasquina Marzola; Pellegrino Masiello; Paul Saftig; Ferruccio Santini; et al. (PLoS ONE)
Growing evidences indicate that proteases are implicated in adipogenesis and in the onset of obesity. We previously reported that the cysteine protease cathepsin K (ctsk) is overexpressed in the white adipose tissue (WAT) of obese individuals. We herein characterized the WAT and the metabolic phenotype of ctsk deficient animals (ctsk-/-). When the growth rate of ctsk-/- was compared to that of the wild type animals (WT), we could establish a time window (5-8 weeks of age) within which ctsk-/-display significantly lower body weight and WAT size as compared to WT. Such a difference was not observable in older mice. Upon treatment with high fat diet (HFD) for 12 weeks ctsk-/- gained significantly less weight than WT and showed reduced brown adipose tissue, liver mass and a lower percentage of body fat. Plasma triglycerides, cholesterol and leptin were significantly lower in HFD-fed-ctsk-/- as compared to HFD-fed WT animals. Adipocyte lipolysis rates were increased in both young and HFD-fed-ctsk-/-, as compared to WT. Carnitine palmitoyl transferase-1 activity, was higher in mitochondria isolated from the WAT of HFD treated ctsk-/- as compared to WT. Together, these data indicate that ctsk ablation in mice results in reduced body fat content under conditions requiring a rapid accumulation of fat stores. This observation could be partly explained by an increased release and/or utilization of FFA and by an augmented ratio of lipolysis/lipogenesis. These results also demonstrate that under a HFD, ctsk deficiency confers a partial resistance to the development of dyslipidemia.